Supply chain sustainability performance indicators: A content analysis based on published standards and guidelines - Muhammad Amad Saeed; Wolfgang Kersten (Logistics Research, 2017)
The goal of this paper is to provide researchers and practitioners with the required guidance to achieve a better assessment of the sustainability-related performance of an organization and its supply chain (SC). In order to achieve this, standards and guidelines covering three sustainability dimensions (eco-nomic, social, and environmental) were analyzed for the identification of sustainability performance indicators (SPIs). A content analysis approach was applied for the data collection and analysis. Twelve international standards and guidelines were identified and selected for the purpose of conducting an analysis to integrate the latest findings on SPIs in sustainable supply chain management (SSCM). The findings of the content analysis revealed 232 original set of instances of sustainability-related infor-mation, of which 46% were related to the environmental dimension, 43% were related to the social dimension and 11% were related to the economic dimension of sustainability. In order to provide a better understanding and evaluation, each sustainability dimension was characterized using attribute categories. A descriptive evaluation of the academic literature, standards, and guidelines resulted in 18 attribute categories. Collected indicators were classified according to these attribute categories. In-depth analysis, restructuring, standardizing of attribute categories and indicators have led to 70 unique and coherent SPIs. Out of which 49% indicators were identified as environmental SPIs, 37% as social SPIs and 14% as economic SPIs. The results revealed a complete lack of agreement among the current standards on how to measure the sustainability-related performance of an organization and its SC.
Keywords: 650; Sustainable supply chain management; performance measurement; content analysis; sustainability performance indicators